Edukasi Gizi Seimbang dan Kesehatan Reproduksi Melalui Media Whatsapp terhadap Pengetahuan Remaja dalam Upaya Pencegahan Stunting : The Effect of Balanced Nutrition and Reproductive Health Education Through Whatsapp Media on Adolescent Knowledge in Stunting Prevention Efforts - Emylisa, Della Awalia; Suryani, Nany; Fathullah, Desya Medinasari; Yudistira, Sigit (Jurnal Ilmu Gizi dan Dietetik, 2023)
Many adolescent nutritional problems occur due to wrong nutritional behavior, such as an imbalance between nutrition and recommended nutritional adequacy and reproductive health for adolescents. This can cause health problems, one of which is stunting. Therefore education on balanced nutrition and reproductive health is needed. The purpose of this study was to determine the effect of education on balanced nutrition and reproductive health whatsapp media on adolescent knowledge efforts to prevent stunting. The subjects of this study were senior high school students aged 16-20 years. The subject was selected using a purposive sampling method with the calculation of the Slovin formula totaling 77 respondents. The research method used is pre-experimental design with the one group pretest-posttest design approach. The research instrument used was a respondent characteristic questionnaire and questionnaire about balanced nutrition to measure respondents knowledge. The test method used to obtain knowledge results before and after being given education on balanced nutrition and reproductive health is the Wilcoxon test. The results of the post-test on balanced nutrition were mostly in the sufficient category, as many as 60 people (77.9%) and the results of the reproductive health post-test were mostly in the good category, as many as 74 people (96.1%). It can be concluded that balanced nutrition education (p=0.001) and reproductive health (p=0.001). It is hoped that students can add to their knowledge about balanced nutrition and reproductive health by applying the knowledge they have been given in their daily lives in an effort to prevent stunting.